PEMANFAATAN Enhallus acoroides SEBAGAI ANTIFOULING - Safira Hari Yanti Mahamude; Faujia Ulfaa Padoma; Rifanli Sumahi; Rinto M. Nur (Fakultas Teknik Universitas Pasifik Morotai, 2024)
Seagrass potential has been explored recently, including the bioactives contained therein. It is known that seagrass has antibacterial, antioxidant, and antifouling activities. The ability of seagrass as antifouling needs to be further developed. The activity of fouling organisms is a problem, especially in the fisheries and shipping sectors. This study aimed to analyze the anti-macrofouling power and identify bioactive compound groups of seagrass Enhalus acoroides methanol extract from Morotai Island Waters. Seagrass samples were obtained from Tanjung Saleh Village, North Morotai District, Morotai Island. Seagrass extraction was carried out using a maceration method and a methanol solvent. The antifouling activity test was conducted using a wood block. Identification of bioactive compounds was carried out qualitatively using a chemical detector. The extraction results showed that the highest yields were leaves, as much as 9.81%, and rhizomes, as much as 6.28%. The identification of bioactive compounds showed that the methanol extract of E. acoroides leaves (EMDEa) contained alkaloid, saponin, and phenol compounds. In contrast, the methanol extract of E. acoroides rhizomes (EMREa) contained saponin and quinone compounds. The results of the anti macrofouling activity test showed that EMDEa has antifouling activity with the discovery of a small quantity of attachment of fouling organisms (46.00%) on wooden blocks, painting treatment with wood paint showed the percentage of fouling organism coverage of 98.33%, painting with varnish of 97.67%, and without painting showed the percentage of fouling organism coverage of 100%.